The state of sexual and reproductive health rights in developing countries: a qualitative review - Raja Ariffin, Raja Noriza; Makmor, Tumin; Mohd Satar, Nurulhuda; Abdul Talib, Muzalwana; Zahari, Rustam Khairi; Hanafi, Hanira (penseejournal.com, 2014)
Objective: To review surveys on sexual and reproductive health rights. The main focus of the review is examining the issues on sexual and reproductive health rights such as family planning, unsafe abortion and role of men as to gain insights on how women are affected by these circumstances. Methods: A qualitative systematic review methodology was carried out by means of thematic synthesis. The scholarly works were searched using databases such as EBSCOhost, Emerald and Web of Science. Results: 18 scholarly works employing survey method involving 18 countries were selected for the review with a total of 184,383 respondents. Conclusion: Women's level of education need to be increased since it can be the most effective platform to advance the acceptance of family planning and increase the demand for planning services. In spite of focusing on sexual and reproductive health rights exclusively on women, a policy on male contraceptive and the right method of information delivery targeting men seems to be necessary.